Testbeam and Laboratory Characterization of CMS 3D Pixel Sensors - Bubna, M; Alagoz, E; Krzywda, A; Koybasi, O; Arndt, K; Bortoletto, D; Shipsey, I; Bolla, G; Kok, A; Hansen, T; Hansen, T; Jensen, G; et al. (Institute of Physics Publishing, 2014)
The pixel detector is the innermost tracking device in CMS, reconstructing interaction vertices and charged particle trajectories. The sensors located in the innermost layers of the pixel detector must be upgraded for the ten-fold increase in luminosity expected with the High- Luminosity LHC (HL-LHC) phase. As a possible replacement for planar sensors, 3D silicon technology is under consideration due to its good performance after high radiation fluence. In this paper, we report on pre- and post- irradiation measurements for CMS 3D pixel sensors with different electrode configurations. The effects of irradiation on electrical properties, charge collection efficiency, and position resolution of 3D sensors are discussed. Measurements of various test structures for monitoring the fabrication process and studying the bulk and surface properties, such as MOS capacitors, planar and gate-controlled diodes are also presented.